Model Pembelajaran TPS Dengan Pendekatan Open-Ended Untuk Meningkatkan Kemampuan Representasi Matematis Siswa - Fernando, Hero; Prihatiningtyas, Nindy Citroresmi; Mariyam, Mariyam (Jurnal Derivat: Jurnal Matematika dan Pendidikan Matematika, 2020)
This study aims to determine students' mathematical representation abilities and motivation by applying Think Pair Share (TPS) learning models with an Open-ended approach. This type of quasi-experimental research with the design of the Nonequivalent Pretest-Posttest Control Group Design. The experimental and control classes were given a pretest and a posttest to see the difference in improvement between the two. This study's population was students of class XI, and the sample was not chosen purely randomly, namely by purposive sampling, and two classes were chosen. The instrument used in this study was a test of students' mathematical representation ability and a student motivation questionnaire. Data analysis using statistical tests namely Independent T-test and descriptive analysis in the form of a percentage formula and the average score. The results of data analysis show that: (1) There is a difference in the increase in students' mathematical representation abilities, and the increase in the experimental class is higher than the control class; (2) The average student motivation in each indicator is in the very high category of 92,14%.Keyword: Think Pair Share, Open-ended Approach, Representation, Motivation